Risk Factors for Endometrial Cancer among Post-menopausal Women in South Africa - RAY, SUDDHASATTWA; Zohorinia, Shadi; Bhattacharyya, Dipankar; Chakravorty, Sayan; Ray, Sonia S (Asian Pacific Journal of Cancer Biology, 2019)
Background: National Cancer Registry of South Africa reported the highest incidence of uterine cancer in Gauteng Proviance. Among uterine cancer patients reported in the Department of Radiation Oncology, Johannesburg Hospital, more than 85% are suffering in endometrial cancers. Here, in this study we tried to explore the relation between factors causing increased blood oestrogen levels, like, contraceptive pills, early menarche and delayed menopause (increases the length of menstruation), nulliparity and overweight by more than 25kg and endometrial cancer among black female population of Greater Johannesburg. In this present study, we also studied how non-sex hormone related factors like hypertension, diabetes, family history, obesity and smoking habits are affecting the occurrence of endometrial cancer in Greater Johannesburg females. Methods: This study is based on post-menopausal female black population of Johannesburg who were physically examined with the help of transvaginal sonar. Their oestrogen level in serum was checked. Their family history, menarche and menopause age, pregnancy and others were collected through questionnaires. Results: The mean age of menarche and menopause was found to be 13.80 and 53.80 years respectively. Hypertension, elevated serum oestradiol level, nulliparity, obesity and diabetes are significantly high among study group. Moreover our study suggests no such relation between smoking habit and endometrial cancer. Conclusion: Continued exposure of endometrium to oestrogen increases the chance of endometrial cancer. The length of menstruation time and nulliparity appeared as vital factors for endometrial cancer. Moreover, adipocytes secreting oestrogen and diabetes are also related to the onset of endometrial cancer among post-menopausal female population.